A literature Review: Determinants of Financial Performance in Local Governments - Yerriandha, Yogga (LPPPIPublishing, 2025)
This study aims to review and synthesize the existing literature on the determinants of local government financial performance in Indonesia, with a particular focus on regions experiencing real fiscal deficits. Under the regional autonomy framework, local governments are required to manage their financial resources independently to support public services and regional development. However, many local governments continue to face fiscal challenges due to limited local revenue capacity and high dependence on central government transfers. Using a literature review approach, this study examines how Local Own-Source Revenue (PAD), capital expenditure, and audit opinion influence local government financial performance. Capital expenditure is also found to play a strategic role in enhancing financial performance through long-term investment in infrastructure, service quality, and economic productivity. Despite extensive empirical evidence, the literature reveals limited attention to the interaction of these factors within local governments experiencing real fiscal deficits. This review highlights the need for more focused analysis in fiscally constrained regions and provides a conceptual foundation for future empirical research aimed at improving sustainable regional financial management.